2013
DOI: 10.1063/1.4803885
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of out-of-plane thermal conductivity of epitaxial YBa2Cu3O7−δ thin films at room temperature measured by photothermal radiometry

Abstract: The out-of-plane (c-axis) thermal conductivities of high-temperature superconducting thin films (YBa2Cu3O7-δ: YBCO) have been measured by photothermal radiometry (PTR) at room temperature. The YBCO samples are in c-axis-aligned epitaxially grown thin films with thicknesses of 250, 500, and 1000 nm. PTR is a noncontact measurement technique for the thermal conductivity and is based on the detection of infrared radiation emitted from a sample heated by a frequency-modulated laser beam. By changing the modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The entire measurement system is arranged on two optical benches with different height in order to avoid the effect of a leak magnetic field from the cryostat on the lasers and optical components such as the Faraday isolators and the balanced detector. The principle and working equations for the experimental technique were essentially consistent with those of photothermal radiometry [19,24], for which we also discussed the uncertainty assessment of the measured thermal conductivity by using this technique. In order to gain sufficiently strong thermoreflectance signals, the YBCO sample surfaces were coated with 159 ± 9 nm sputtering films of platinum as a reflecting layer against the probing laser light.…”
Section: Experimental Apparatusmentioning
confidence: 66%
See 4 more Smart Citations
“…The entire measurement system is arranged on two optical benches with different height in order to avoid the effect of a leak magnetic field from the cryostat on the lasers and optical components such as the Faraday isolators and the balanced detector. The principle and working equations for the experimental technique were essentially consistent with those of photothermal radiometry [19,24], for which we also discussed the uncertainty assessment of the measured thermal conductivity by using this technique. In order to gain sufficiently strong thermoreflectance signals, the YBCO sample surfaces were coated with 159 ± 9 nm sputtering films of platinum as a reflecting layer against the probing laser light.…”
Section: Experimental Apparatusmentioning
confidence: 66%
“…In our previous paper [19], we showed that the out-of-plane thermal conductivity of epitaxially grown YBCO thin films exhibited thickness dependence even at room temperature. This result may have been due to the quite broad spectral distribution of phonons responsible for the thermal transport perpendicular to the CuO 2 planes.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations